A Changing of the Guard: Regional Planning in Ottawa, 1945-1974 - Fullerton, Christopher (Urban History Review / Revue d'histoire urbaine, 2005)
This paper examines the evolution of planning in Ottawa's metropolitan region between 1945 and 1974—a period of significant change in the city's planning history. As elsewhere, planners and policy-makers in Ottawa were coming under increasing pressure to make effective public participation a legitimate part of planning activities and to consider more seriously the potential quality-of-life impacts of their planning decisions, most notably those related to the provision of transportation infrastructure. Yet it was also in the late 1960s that the federal government was forced to concede its long-standing, yet unofficial, control of regional planning for the Ottawa area to the newly created Regional Municipality of Ottawa-Carleton (RMOC). Accordingly, creation of the RMOC's first official plan was a contentious process that, in the end, enabled the continuation of postwar suburban development trends while also incorporating a “transit first” philosophy granting precedence to public transit over all forms of road construction and widening. The direction taken in its first official plan also enabled the RMOC to demonstrate that it, rather than the federal government, would from then on play the lead in regional planning.